Epidemiology of Mastitis Pathogens in Dairy Cattle in Cauvery Delta Region of Tamil Nadu - Jayalakshmi, K.; Palanivel, K. M.; Sumathi, D.; Vijayarajan, A.; Prasath, N. Babu (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during the year 2024 from January to December for a period of one year at Veterinary Clinical Complex, Orathanadu. The aim of the study was to identify the most common etiology, prevalence and risk factors associated with the mastitis in the dairy cattle in Cauvery Delta region of Tamil Nadu. A total of 16049 cattle and 275 buffalo were presented to VCC, VC&RI, Orathanadu, of which 529 cases (cattle-527, buffalo-2) were mastitis. A total of 130 milk samples were collected from 124 mastitis cases for bacterial culture. The Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Coagulase negative staphylococci, Streptococcus spp and Bacillus spp were isolated and confirmed by PCR. Among the bacterial isolates, the Klebsiella pneumoniae (62.50%) was the predominant bacteria followed by Coagulase- negative staphylococci (16.34%), Bacillus spp (5.77%), Staphylococcus aureus (4.81%), Streptococcus spp (4.81%), Escherchia coli (2.88%), and Pseudomonas aeruginosa (2.88%). The prevalence of mastitis in cattle and buffalo were 3.28 and 0.73%, respectively. The Crossbred Jersey cows were more susceptible than Crossbred Holstein Friesian and Indigenous breeds. The lactation stage had highly influenced the occurrence of disease. The animals in second and third lactation, especially in the early stage of lactation at 5–7 years were highly susceptible to mastitis. The prevalence of disease was high during the rainy season (33.07%) followed by autumn (24.0%), winter (22.87%) and summer (20.06%). In this study, the environmental mastitis pathogens was highly prevalent than contagious pathogen. It could be controlled by reducing stress and increasing host resistance by supplementation of vitamin E and selenium.